2018
DOI: 10.1038/s41598-017-18925-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between arsenic metabolism gene polymorphisms and arsenic-induced skin lesions in individuals exposed to high-dose inorganic arsenic in northwest China

Abstract: Individuals in a given environment contaminated with arsenic have different susceptibilities to disease, which may be related to arsenic metabolism, age, gender, genetics and other factors. This study recruited 850 subjects, including 331 cases and 519 controls, from populations exposed to high levels of arsenic in drinking water in northwest China. Genotypes were determined using a custom-by-design 48-Plex SNPscanTM kit. The results indicated that subjects who carried at least one C allele for GSTO1 rs1119197… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 60 publications
0
46
0
Order By: Relevance
“…The occurrence of arsenic in groundwater and food is associated with an increased risk of skin, liver, kidney and lung cancers as well as other diseases such as atherosclerosis and cardiovascular diseases, diabetes, hypertension and neurological diseases (Alzheimer, Parkinson). Moreover, the International Agency for Research on Cancer has put arsenic and its compounds in the group of the first carcinogenic compounds whose action has been proven epidemiologically (KULSHRESTHA et al 2014;GAMBO-LOIRA et al, 2017;LUO et al, 2018). Initially, the daily intake of arsenic was 15 μg/kg of body weight, but studies have shown that even lower doses can contribute to the development of lung, bladder and skin cancers.…”
Section: Pathogenesis Associated With Arsenic Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of arsenic in groundwater and food is associated with an increased risk of skin, liver, kidney and lung cancers as well as other diseases such as atherosclerosis and cardiovascular diseases, diabetes, hypertension and neurological diseases (Alzheimer, Parkinson). Moreover, the International Agency for Research on Cancer has put arsenic and its compounds in the group of the first carcinogenic compounds whose action has been proven epidemiologically (KULSHRESTHA et al 2014;GAMBO-LOIRA et al, 2017;LUO et al, 2018). Initially, the daily intake of arsenic was 15 μg/kg of body weight, but studies have shown that even lower doses can contribute to the development of lung, bladder and skin cancers.…”
Section: Pathogenesis Associated With Arsenic Compoundsmentioning
confidence: 99%
“…It is interesting that the susceptibility to diseases associated with arsenic poisoning may vary in people of different ages, sexes or genetically adapted (LINBERG et al, 2007;ENGSTROM et al, 2007;TSENG et al, 2009;TORRES-SANCHEZ et al, 2016;LUO et al, 2018;STOJSAVLJEVIĆ et al, 2019;SOZA-RIED et al, 2019). For instance, in children an increased methylation of inorganic forms of arsenic and its urinary excretion were observed.…”
Section: Arsenic Medicine or Poison? -Dualism Of Arsenic Influence On The Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…As AISL are widely accepted as the major early manifestation of arsenic toxicity6 and may be an indicator of susceptibility to more serious arsenic-induced health hazards,7 it is critical to identify people who are at risk as early as possible to prevent the onset or delay the progression of serious health problems. Several possible mechanisms such as genetic differences,8 oxidative stress9 and epigenetic dysregulation10 may explain arsenic poisoning. Previous studies also suggested that arsenic methylation in vivo is associated with metabolic syndrome 11 12…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of arsenic in crops and arsenic contamination in water are the main causes of arsenic poisoning and carcinogenesis [2,3] . According to the survey, the arsenic concentration in drinking water is positively correlated with the incidence of lung cancer and bladder cancer [4,5] . Microbioremediation technology has the advantages of low cost, high efficiency, no secondary pollution, and has great potential in the restoration of natural water bodies.…”
Section: Introductionmentioning
confidence: 99%